Synthesis of the topological structure of rood freight transport system - Baublys, Adolfas; Išoraite, Margarita (Transport, 2006)
Synthesis of regional road transport freight system's topological structure enables the assessment of impact exercised by various structural characteristics on the functioning of the system. Consequently, it should increase the quality of project solutions in the stage of system structural synthesis. Models of optimization and simulation (included into the simulation procedure of optimization of topological structure) have other possibilities as well. For instance, simulation model enables the solution of various objectives of functional analysis of systems, such as the efficiency comparison analysis of stability of structure undergoing the changes of meanings of system's parameters, the analysis of managing impacts of various types, loading technologies, etc.First Published Online: 27 Oct 2010